Antimicrobial Resistance Profile of Bacteria Isolated from Canine and Feline Samples at the Preventive Veterinary Laboratory of the Federal University of Rio Grande do Sul (UFRGS) - Brazil - Vieira, Tatiana Regina; Zenatto, Karoline; Sambrano, Gustavo Enck; Cardoso, Marisa (Acta Scientiae Veterinariae, 2022)
Background: Antimicrobial resistance (AMR) is a major global health threat. In small animals such as dogs and cats, antimicrobials are most commonly prescribed for skin and genitourinary diseases; therefore, the AMR of bacteria involved in these infections should be monitored. In addition, the results of antimicrobial susceptibility testing (AST) may be interpreted as a local epidemiological history of AMR. The Preventive Veterinary Medicine Laboratory (PVML) received clinical samples from dogs and cats for bacterial isolation and AST. Thus, this study aimed to assess the AMR of bacteria isolated from the samples of dogs and cats received at the Preventive Veterinary Medicine Laboratory (PVML). Materials, Methods & Results: Data from bacteriological examinations performed at the PVML of the Universidade Federal do Rio Grande do Sul (UFRGS) during 5 years were analyzed. Skin and ear canal samples were inoculated in 5% sheep blood agar, and urine samples were streaked on CHROMagar™ orientation. After incubation at 36±1°C for up to 72 h, identification and AST were performed according to routine protocols. Of 1,534 samples submitted to the PVML, 1,086 (70.8%) were collected from dogs and 29.2% from feline patients. Otological swabs (n = 533, 49.1%) were the most frequent samples from dogs, while cat urine samples (n = 384, 84.8%) predominated by far. Considering the canine samples, no bacterial growth (NBG) was observed in 443 (40.8%) samples, while only one colony type was noted in 516 (47.5%) samples. Gram-positive bacteria (n = 298) were more frequent than gram-negative bacteria (n = 77) in the skin. In urine samples, gram-negative bacteria (n = 94) were isolated more frequently than gram-positive bacteria (n = 47). In feline samples, a high number of NBG (n = 308, 68%) was observed. Gram-positive (n = 22) was predominant in comparison to gram-negative bacteria (n = 9) in cultures from the ear and skin swabs. Enterococcus spp. and Escherichia coli were the most frequently identified bacteria in urine samples. Among the Staphylococcus sp. strains of any origin, AMR frequency varied from 4.22% (amikacin) to 50.70% (sulfa/trimethoprim). Enterococcus spp. showed AMR frequencies from 12.5% (amoxicillin/clavulanic acid) to 62.06% (enrofloxacin). Among the gram-negative genera, E. coli presented AMR frequencies from 10.20% (gentamicin) to 60.0% (neomycin). The frequency of AMR was stable over time, and a profile of much higher resistance to fluoroquinolones in comparison to beta-lactams was observed. Discussion: The recurrence of skin and urinary infections implies the need for frequent treatment with antibiotics, which exerts selection pressure for resistance and multidrug resistance. In this study, the frequency of multidrug resistance was low, and the resistance to the tested antimicrobials showed high variation. However, a trend of high resistance to the fluoroquinolone group was observed in contrast to the low resistance to beta-lactams. This trend was consistent among the isolated bacteria, regardless of the type of sample or origin. The overprescription of fluoroquinolones in small animal practices has been widely documented in several countries. However, this class of antimicrobials, is highly prioritized for the treatment of infections in humans. Therefore, the selection of resistant strains has gained special emphasis, especially when considering the possibility of the transmission of resistant bacteria between pets and humans. In summary, the results of bacteriological tests conducted at the PVML-Universidade Federal do Rio Grande do Sul confirmed that ubiquitous bacteria predominate in clinical samples of dogs and cats. The high frequency of resistance to the fluoroquinolone group, while a predominance of susceptible strains in the first-choice drugs such as amoxicillin/clavulanic acid, may indicate excessive and empirical use of the second-choice drugs in clinical practice. Keywords: otitis, dermatitis, urinary infection, dogs, cats, antibiotic resistance, AMR.